Conflict Management in Student Groups - a Teacher’s Perspective in Higher Education - Markus Borg; Joakim Kembro; Jesper Notander; Catarina Petersson; Lars Ohlsson (Högre Utbildning, 2011)
Students working in groups is a commonly used method of instruction in higher education, popularized by the introduction of problem based learning. As a result, management of small groups of people has become an important skill for teachers. The objective of our study is to investigate why conflicts arise in student groups at the Faculty of Engineering at Lund University and how teachers manage them. We have conducted an exploratory interdepartmental interview study on teachers' views on this matter, interviewing ten university teachers with different levels of seniority. Our results show that conflicts frequently arise in group work, most commonly caused by different levels of ambition among students. We also found that teachers prefer to work proactively against conflicts and stress the student’s responsibility. Finally, we show that teachers at our faculty tend to avoid the more drastic conflict resolution strategies suggested by previous research. The outcome of our study could be used as input to future guidelines on conflict management in student groups.